Is Parity a Predictor of Neonatal Death in Indonesia? Analysis of the 2017 Indonesia Demographic and Health Survey - Ratna Dwi Wulandari1 , Agung Dwi Laksono2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One factor that is thought to have a close relationship with neonatal deaths is parity. This is a problem for Indonesia which has the cultural characteristics of a large number of children is something positive. The study used the 2017 IDHS data. With stratification and multistage random sampling, 36,548 women aged 15-49 years with live births in the last 5 years were sampled. The final analyzed using a Binary Logistic Regression test. Multiparous women in Indonesia have a higher percentage of neonatal deaths than multiparous women. But the difference in parity between primiparous and multiparous was found not to be a predictor of neonatal death in Indonesia. Three other variables were found to be proven, predictors. Women who were not employed were 0.576 times more likely than women employed for neonatal death (OR 0.576; 95% CI 0.407-0.814). Women who did antenatal care ?4 times were 2.332 times more likely than women who had ANC <4 times to experience neonatal death (OR 2.332; 95% CI 1.519-3.578). Women who did not experience a complication during delivery were 0.457 times more likely than women who had a complication during delivery for neonatal death (OR 0.457; 95% CI 0.317-0.659). The study concluded that parity was not a predictor of neonatal death in Indonesia. Other variables that were proven to be predictors are employment status, antenatal care, and complications during pregnancy